Decision Support System For Hiring Honorary Teachers At State Junior High School 12 Kota Bengkulu Using The Simple Multi Attribute Rating Technique Method - Silvy Dwi Nurhalifah; Yupianti Yupianti; Indra Kanedi (UNIVED Press, 2024)
Honorary teachers are auxiliary teachers who are given teaching time according to the number of teaching hours with a salary in accordance with the hours of lessons they teach and have been arranged by several schools for the smooth teaching process. The acceptance of honorary teachers carried out at junior high school 12 Kota Bengkulu is still done onventionally without paying attention to quality and competence in the selection process, resulting in human error, open opportunities for nepotism activities. For this reason, a decision support system is needed that can help solve these problems. The method implemented in this system is SMART (Simple Multi Attribute Rating Technique). The simplicity of the SMART method in analyzing responses, responding to the wishes of decision makers, and the simplicity of calculations in decision making. This SMART method aims to facilitate the decision making of honorary teacher acceptance at SMP Negeri 12 Bengkulu City so as not to use the manual system anymore. From the results of the tests that have been carried out, it can be concluded that the honorary teacher acceptance system with the SMART method can provide a good and more objective assessment.